Smad3 initiates oxidative stress and proteolysis that underlies diaphragm dysfunction during mechanical ventilation. Issue 1 (December 2017) - Tang, Huibin; Kennedy, Catherine; Lee, Myung; Gao, Yang; Xia, Hui; Olguin, Francesca; Fraga, Danielle; Ayers, Kelsey; Choi, Sehoon; Kim, Michael; Tehrani, Amir; Sowb, Yasser; et al.
Abstract Prolonged use of mechanical ventilation (MV) leads to atrophy and dysfunction of the major inspiratory muscle, the diaphragm, contributing to ventilator dependence. Numerous studies have shown that proteolysis and oxidative stress are among the major effectors of ventilator-induced diaphragm muscle dysfunction (VIDD), but the upstream initiator(s) of this process remain to be elucidated. We report here that periodic diaphragm contraction via phrenic nerve stimulation (PNS) substantially reduces MV-induced proteolytic activity and oxidative stress in the diaphragm. We show that MV rapidly induces phosphorylation of Smad3, and PNS nearly completely prevents this effect. In cultured cells, overexpressed Smad3 is sufficient to induce oxidative stress and protein degradation, whereas inhibition of Smad3 activity suppresses these events. In rats subjected to MV, inhibition of Smad3 activity by SIS3 suppresses oxidative stress and protein degradation in the diaphragm and prevents the reduction in contractility that is induced by MV. Smad3's effect appears to link to STAT3 activity, which we previously identified as a regulator of VIDD. Inhibition of Smad3 suppresses STAT3 signaling bothin vitro andin vivo . Thus, MV-induced diaphragm inactivity initiates catabolic changes via rapid activation of Smad3 signaling. An early intervention with PNS and/or pharmaceutical inhibition of Smad3 may prevent clinical VIDD.